Utilization rate of uncontrolled donors after circulatory death‐a 3‐year single‐center investigation. Issue 8 (3rd June 2020) - Lazzeri, Chiara; Bonizzoli, Manuela; Fulceri, Giorgio Enzo; Guetti, Cristiana; Ghinolfi, Davide; Li Marzi, Vincenzo; Migliaccio, Maria Luisa; Peris, Adriano
Abstract: Background: Effectiveness of uncontrolled donation after circulatory death (uDCD) has been recently reported to be 75% according to data coming from some European countries in 2016, but few data are to date available on this topic. Methods: We assessed the utilization rate (as the percentage of donors who were converted into actual donors) in 37 uDCDs consecutively enrolled at our Center (Careggi Teaching Hospital) from June 2016 to June 2019. Results: In three cases, the family did not give consent for donation (3/37, 8.1%). Among the 37 potential uDCDs, 22 became actual donors (22/37, 59%), with 10 livers and 38 kidneys being transplanted, respectively. Fifteen livers were recovered (15/37, 68%), and 10 livers were transplanted (10/15, 67%). Forty‐two kidneys were procured and 38 organs transplanted. The overall effectiveness was 78%. Conclusions: According to our 3‐year experience, uncontrolled DCDs do represent an additional means of increasing the number of transplanted organs (kidneys and livers) with an acceptable utilization rate. Research on organ viability assessment (for both livers and kidneys from uDCDs) is still in its infancy, and there is probably space for a further wider use of organs from uDCDs.